Extent and nature of duplication in PROSPERO using COVID-19-related registrations: a retrospective investigation and survey - Ruth Walker; Lesley Stewart; Lucy Beresford (BMJ Open)
Objectives During COVID-19, the International Prospective Register of Systematic Reviews (PROSPERO) experienced a surge in registrations for COVID-19-related systematic reviews, and duplication of research questions became apparent. Duplication can waste funding, time and research effort and make policy making more difficult.This project explored the extent of and reasons for duplication of COVID-19-related systematic review registrations in PROSPERO during the pandemic.Design Retrospective analysis of COVID-19-related registrations in PROSPERO, and a qualitative survey.Setting PROSPERO was searched for registrations related to four COVID-19 research areas: epidemiology, rehabilitation, transmission and treatments.Methods Records identified were compared using Population, Intervention/Exposure, Comparator, Outcome, Study Design (PICOS) elements of PROSPERO registration forms. Registrations with similar or identical PICOS were evaluated further as ‘duplicates’.Authors of ‘duplicate’ registrations were invited to complete a survey asking whether they searched PROSPERO prior to registration, identified similar reviews and, if so, why they continued with their review.Results 1054 COVID-19 reviews were registered between March 2020 and January 2021, of which 138 were submitted when at least one similar protocol was already registered in PROSPERO. Duplication was greatest in reviews of COVID-19 treatments; for example, there were 14 similar reviews evaluating the efficacy of hydroxychloroquine.From 138 authors invited to take part in the survey, we received 41 responses. Most respondents said that they identified similar reviews when they searched PROSPERO prior to registration. Main reasons given for ‘duplication’ were differences in PICOS or planned analyses (n=13), poor quality of previous registrations (n=2) and the need to update evidence (n=3).Conclusions This research highlights that registration of similar and duplicate systematic reviews related to COVID-19 in PROSPERO occurred frequently. Awareness of research waste is required, and initial checking for similar reviews should be embedded within good review practice.